Real time emulator for parallel connected dual-PMSM sensorless control - Khaldoune Sahri; Maria Pietrzak-David; Lotfi Baghli; Abdelaziz Kheloui (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper presents a real-time emulator of a dual permanent magnet synchronous motor (PMSM) drive implemented on a field-programmable gate array (FPGA) board for supervision and observation purposes. In order to increase the reliability of the drive, a sensorless speed control method is proposed. This method allows replacing the physical sensor while guaranteeing a satisfactory operation even in faulty conditions. The novelty of the proposed approach consists of an FPGA implementation of an emulator to control the actual system. Hence, this emulator operates in real-time with actual system control in healthy or faulty mode. It gives an observation of the speed rotation in case of fault for the sake of continuity of service. The observation of the rotor position and the speed are achieved using the dSPACE DS52030D digital platform with a digital signal processor (DSP) associated with a Xilinx FPGA.